MENELUSURI WARISAN KEBIJAKAN PENDIDIKAN ISLAM DI MASA KOLONIAL BELANDA - Irwan, Irwan; Ishomuddin, Ishomuddin; Faridi, Faridi (Fitrah, 2024)
The aim of this research is to analyze the existence and policies of Islamic education during the Dutch colonial period. This research is necessary because the existence of Islamic education in Indonesia is inseparable from a historical process that has experienced ups and downs. The history of education in Indonesia has undergone remarkable changes, closely tied to the era of colonialism. A qualitative method with a descriptive approach is employed to analyze the data, which is obtained from literature after a thorough study of relevant sources regarding the policies of Islamic education during the Dutch colonial period. The study finds that the Dutch hegemony in shaping policies for Islamic education in Indonesia, particularly by Islamic educational institutions, is based on political, ideological, and cultural reasoning in the colonial style to enforce its influence over the indigenous people of Indonesia. Consequently, this analysis reveals that the policies issued by the Dutch government during its colonial period in Indonesia often disadvantaged the Muslim community. In conclusion, these findings indicate that Islamic education became less flexible and challenging to develop. Nevertheless, efforts to fight for and sustain Islamic education continue through the establishment of institutions such as pesantren (Islamic boarding schools) and madrasahs, despite facing limitations and challenges.